Driving Excellence: How Innovation Strategies and Organizational Commitment Shape Management Control Systems (MCS) with Organizational Culture as the Key Moderator - Ridwan Saleh; Yudhistira Adwimurti; Rahmani, Hani Fitria; Delina Herdian Septiani (Sean Institute, 2024)
This research aims to analyze the influence of innovation strategy and organizational commitment on the effectiveness of Management Control Systems (MCS) with organizational culture as a moderating variable in cyclical and non-cyclical companies listed on the Indonesia Stock Exchange (BEI) in 2023. Using a quantitative approach with a cross design -sectional, data was collected through questionnaires from 92 middle and upper level managers in cyclical and non-cyclical companies. Hierarchical regression analysis was used to test the hypothesis. The research results show that innovation strategy and organizational commitment have a significant positive effect on MCS effectiveness. Organizational culture is proven to moderate the relationship between innovation strategy and MCS effectiveness, as well as between organizational commitment and MCS effectiveness. The research model explained 58.7% of the variation in MCS effectiveness. These findings emphasize the importance of aligning innovation strategies, building organizational commitment, and creating a supportive culture to increase the effectiveness of MCS in cyclical and non-cyclical companies in Indonesia. This research provides a theoretical contribution to the development of MCS literature by integrating the perspectives of innovation strategy, organizational commitment, and organizational culture. Practically, the research results provide insight for managers of cyclical and non-cyclical companies in Indonesia in designing and implementing effective MCS, taking into account organizational contextual factors.